2016
DOI: 10.1038/srep37506
|View full text |Cite
|
Sign up to set email alerts
|

Close relationship between a dry-wet transition and a bubble rearrangement in two-dimensional foam

Abstract: Liquid foams are classified into a dry foam and a wet foam, empirically judging from the liquid fraction or the shape of the gas bubbles. It is known that physical properties such as elasticity and diffusion are different between the dry foam and the wet foam. Nevertheless, definitions of those states have been vague and the dry-wet transition of foams has not been clarified yet. Here we show that the dry-wet transition is closely related to rearrangement of the gas bubbles, by simultaneously analysing the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Indeed, 5.00 g and 10.00 g EW protein meringue batters had ϕ values of around 0.61 and 0.65, respectively, which is close to the point at which a system occurs as a "bubbly liquid" rather than as wet foam (Furuta, Oikawa, & Kurita, 2016;Langevin, 2017). In contrast, GH protein containing batters had ϕ values of at least 0.77, which is well in the range of values at which a system occurs as a wet foam (Furuta et al, 2016;Langevin, 2017). In any case, batters containing GHs had better texture and airiness than batter containing only EW protein.…”
mentioning
confidence: 60%
“…Indeed, 5.00 g and 10.00 g EW protein meringue batters had ϕ values of around 0.61 and 0.65, respectively, which is close to the point at which a system occurs as a "bubbly liquid" rather than as wet foam (Furuta, Oikawa, & Kurita, 2016;Langevin, 2017). In contrast, GH protein containing batters had ϕ values of at least 0.77, which is well in the range of values at which a system occurs as a wet foam (Furuta et al, 2016;Langevin, 2017). In any case, batters containing GHs had better texture and airiness than batter containing only EW protein.…”
mentioning
confidence: 60%
“…The liquid content measured in the DFA100 apparatus during foam formation and decay stages varied between 10% and 30% depending on the SAS type, solution concentration, and investigated foam level. These Φ values directly indicated that the foams were in a transient form [17][18][19][20].…”
Section: Analysis Of Synergistic Effect Originmentioning
confidence: 92%
“…In a dry foam, the liquid films are sometimes rearranged and the it induces coarsening of bubbles over time 1 , 2 . It has also been reported that bubbles are simply stretched when a bubble collapses 13 . As the liquid fraction increases and the dry foam is transformed into a wet foam, the bubbles are rearranged more smoothly 14 , exhibiting enhanced fluidity.…”
Section: Introductionmentioning
confidence: 94%
“…They are also widely seen in daily life, from foods and beverages to pharmaceuticals, cleaning products, cosmetics and building materials such as building insulation and flame-retardant barriers 1 – 14 . Foams can take three states depending on the liquid fraction ; these are called dry, wet and bubbly foams, from low to high 13 , 14 . The dry state is made up of polyhedral bubbles and is more jammed than the wet state, which consists of round bubbles.…”
Section: Introductionmentioning
confidence: 99%